REVITALISASI KEMITRAAN TEMBAKAU VIRGINIA DI JAWA TIMUR - Samsuri Tirtosastro; Taufik Iskandar (BUANA SAINS, 2011)
Cigarette industries in Indonesia especially nowadays still need to import some raw ingredients. The highest import for 10 years (2001-2010) is from China i.e. for about 28,288,197 ton/year or 53.38% from import total of the total import of 52,999,855 kg/year with a value of USD 127.149.050/year. The price of dried tobacco leaves from China is only USD 1,996/kg or 83.84% from the average price of import dried tobacco leaves. Base on these data, it is showed that most local cigarette industries need to have dried tobacco leaves with medium quality and low price. Opportunity for East Java to develop virginia tobacco is high enough. East Java not only has quite potential area, but also has technology packages which are sufficient enough to increase productivity up to 2,000kg/ha or more. The weakness is the system for guiding farmers. There is no link in the technology partnership, production tools, furthermore marketing resulted in low productivity and quality. As a fancy product there should be a link between farmers as producers and tobacco industries as consumers for all sub-systems of virginia tobacco farming business. Cooperation of producers, consumers, and local governments is the basic framework of the system for guiding. Producers and consumers had more cooperation in the aspects of production and quality improvement. Local government regulations governed on all parties working together based on justice. Farmers as producers are obliged to apply the technology built and sell dried tobacco leaves according to the company's pricing agreement builder